2020
DOI: 10.9740/mhc.2020.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Trichotillomania associated with a 25-hydroxy vitamin D deficiency: A case report

Abstract: Vitamin D deficiency has been correlated with non-scarring alopecia including alopecia areata or female pattern hair loss. It was theorized that hair loss secondary to vitamin D deficiency in patients susceptible to trichotillomania may exacerbate this obsessive-compulsive disorder. Though vitamin D deficiency is common, especially among patients suffering from neuropsychiatric disorders, its correlation with trichotillomania is not well reported. Two female patients suffering from trichotillomania defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…38 Finally, a correlation between vitamin D and trichotillomania, an OCD-related disorder, was highlighted in 2 women who improved after a treatment with vitamin D supplementation. 46 In our sample, no differences in vitamin D levels were noted between men and women, or between medicated or unmedicated patients, or among patients with different comorbidities. We only observed that patients (13) taking SGAs showed higher vitamin D values than patients (4) taking FGAs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…38 Finally, a correlation between vitamin D and trichotillomania, an OCD-related disorder, was highlighted in 2 women who improved after a treatment with vitamin D supplementation. 46 In our sample, no differences in vitamin D levels were noted between men and women, or between medicated or unmedicated patients, or among patients with different comorbidities. We only observed that patients (13) taking SGAs showed higher vitamin D values than patients (4) taking FGAs.…”
Section: Discussionmentioning
confidence: 51%
“…Another recent study revealed that patients with PANDAS showed a reduced level of vitamin D in comparison with healthy control subjects, independently from the seasons 38 . Finally, a correlation between vitamin D and trichotillomania, an OCD-related disorder, was highlighted in 2 women who improved after a treatment with vitamin D supplementation 46 …”
Section: Discussionmentioning
confidence: 95%
“…Vitamin D also improves hair growth by complex molecular pathways regulating the interaction between dermal papillary cells and surrounding epithelial stem cells. 29 To conclude, vitamin D supplementation along with psychopharmacological management may help to decrease the urge to pull hair and improve hair growth in TTM.…”
Section: Studymentioning
confidence: 99%
“…Vitamin D in a daily dose of 1000 IU for 3–5 months, reduced the urge to pull in TTM. Vitamin D also improves hair growth by complex molecular pathways regulating the interaction between dermal papillary cells and surrounding epithelial stem cells 29 …”
Section: Vitamin D In Trichotillomaniamentioning
confidence: 99%
See 1 more Smart Citation